FOLK ASSOCIATIONS IN RHYMING SLANG - Yu.V. Gorshunov (Многоязычие в образовательном пространстве)
The purpose of the article is to identify and describe examples of rhyming slang with folklore associations. Some of the rhymes are based on the names of well-known characters in nursery rhymes, or on the use of catchy names of rhymes that make up the treasure trove of folklore of English-speaking countries aimed at children. Other rhymes are based on the lines of some rhymes that have come into wide use and are known to the bearers of English-speaking culture from childhood. Expressions of rhyming slang associated with nursery rhymes refer to folklore images and reflect folk traditions and legends. The nursery rhymes underlying the rhymes are cultural items that are reflected in the collective memory of English speakers and are thus included in the current background knowledge and background knowledge of the cultural heritage. The topic is covered by using examples of rhyming slang samples selected by a continuous sampling method from authoritative dictionaries of general and rhyming slang. The research field included 20 allusive rhymes with folklore associations. The selected rhymes are considered in alphabetical order and provided with appropriate linguistic, cultural and sociocultural commentary. Undoubtedly, allusive rhymes deserve the attention of specialists in English linguistic culture, since rhyming slang, built on allusions to nursery rhymes, has not yet been the subject of special analysis. The results of the study may be useful and interesting for researchers specialising in intercultural communication, linguoculturology, linguistic and regional studies, contrastive linguistics of the English and Russian languages, foreign (English) history and literature, speech culture and the practice of teaching English.